Polls and Elections: Swift Boating Reconsidered: News Coverage of Negative Presidential Ads. Issue 4 (27th October 2016) - Major, Mark; Andersen, David J.
Abstract : Negative political ads are increasingly ubiquitous in presidential campaigns but most of the public do not directly observe these ads. Instead they become aware of these negative attacks through the press. Recent scholarship finds that the news media incentivizes presidential campaigns to go negative as it will generate more free coverage compared to positive advertisements. However, scholarship has yet to examine the framing of this free coverage. Through a content analysis of New York Times, Washington Post, and USA Today's coverage of the controversial Swift Boat Veteran's for Truth ads during the 2004 presidential election, this study evaluates whether free media is synonymous with wanted coverage. We find that news coverage provides both benefits and disadvantages for the presidential campaigns associated with the negative ads.